FORMAL ANALYSIS OF WILHELMINA STATUE COLLECTION OF MAKASSAR CITY MUSEUM - Satriadi Satriadi; Muh. Saleh Husain (JURNAL PAKARENA, 2021)
This research seeks to explain to art observers, especially visitors to the Makassar city museum related to the existence of one of the collections of statues in the museum building. To explain the statute, a search of the library and other relevant sources was carried out. To obtain data on realist analysis of statues, data collection is collected using instruments analyzed based on the realist elements of sculpture, observation, documentation, and interviews. The subject of this research is the Wilhelmina statue collection of the Makassar city museum. The results of the analysis revealed that the statue is a realist statue with the form of a portrait statue or bust statue. The statue depicts the figure of a queen who came from the Netherlands. The existence of the statue in the city of Makassar is historical evidence that reminds us of colonialism that occurred in Makassar in the past. The results of this analysis can help explain one of the historical pieces of evidence of Dutch colonialism that has occurred in Makassar.